A CASE STUDY ON WEIGHT LOSS INVOLVING A WOMAN UTILISING WET CUPPING THERAPY, QURAN MEMORISATION AND PHYSICAL EXERSICE - Wilda Fasim Hasibuan; Nurdjanah (International Islamic Medicine Forum, 2025)
This study seeks to elucidate the weight loss process using cupping, walking, and Quranic memorization. Characterized a process that transpires over an extended duration. This research employs a single subject research design (SSRD) utilizing a baseline and treatment framework (ABAB), with treatment administered according to the status of the obese patient. The study's results indicated a reduction in body weight throughout the three weight loss phases. The ABAB design was implemented for the cupping procedure, walking, and Quran memorization, as all were tailored to the situation of the obese patient. The conclusion is that thorough measures are essential, beginning with body weight, blood pressure, step count, and the quantity of Quranic verses remembered. ABSTRAK Penelitian ini bertujuan menggambarkan proses penurunan berat badan dengan bekam, jalan kaki dan menghafal Al-Quran. Digambarkan proses yang tidak terjadi dalam waktu singkat. Metode penelitian ini menggunakan single subject research design (SSRD) dengan desain baseline dan treatment (ABAB), treatment dilakukan berdasarkan kondisi penderita obesitas. Hasil penelitian yang diperoleh bahwa terjadi penurunan berat badan selama menjalankan 3 proses penurunan berat badan. ABAB desain dilakukan pada metode bekam, jalan kaki dan menghafal Al-Quran, karena semuanya dilakukan disesuaikan dengan kondisi penderita obesitas. Kesimpulan yang dapat diambil adalah dibutuhkan pengukuran yang komprehensif, mulai dari pengukuran berat badan, tekanan darah, jumlah langkah jalan kaki, dan jumlah ayat Al-Quran yang dihafal.